Analysis of Interpersonal Meaning Realized in Undergraduate Students’ News Item Texts - Pratama, Arif; Dwi Areni, Galuh Kirana (Journal of English Language and Education, 2025)
In the interpersonal meaning, language is seen as a tool to maintain the relationship between the speaker/writer and the audience/reader. The use of interpersonal meaning to interpret written texts is very useful to find out the writer's purpose in conveying information or giving suggestions to readers. This study aims to investigate the interpersonal meaning realized in 20 news item texts of fourth semester students of English Education Study Program academic year 2023/2024, Universitas Negeri Semarang. This study employed Eggins' (2004) Systemic Functional Linguistics (SFL) theory and Halliday and Matthiessen (2014) as the research framework. This research uses the case study method because it focuses on analyzing and describing a phenomenon comprehensively. This research analyzes the realization of interpersonal meaning through mood system and modality system in students' news item texts. Based on the findings, it is found that most students use declarative mood in their news item texts. There are 379 clauses that show declarative mood in both positive and negative forms. In the modality system, two types were found, which are modalization and modulation. Modalization type is most often found in news item texts, with 38 clauses using modalization. It can be said that the students have realized the interpersonal meaning in their news item texts. This can be seen from the use of mood system and modality system in the text.